Satisfaction of Basic Psychological Needs and its Impact on Mental Health among Undergraduate Students in Select Gulf Universities - Ehab Omara; Kashef Zayad; Majid Al-Busafi; Asma Al-Attiyah; Nasser Al-Rawahi; Ahmed Al-Haramleh; Ali Al-Shamli; Khalifa Al-Jadidi; Abdullah Al-Qaidi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The current study aims to identify the perceptions of a sample of students in some Gulf universities about the extent to which the universities satisfy their basic psychological needs. Moreover, the study seeks to investigate whether these perceptions predict the level of students' mental healthf. To achieve these goals, the Arabic versions of: (1) Basic Psychological Needs Satisfaction Frustration Scale, (2) Warwick-Edinburgh Mental Wellbeing Scale, and (3) The Warwick-Edinburgh Mental Wellbeing Scale (2) from the Beck Depression Inventory-II were applied to a sample of 608 university students in three Gulf countries: Oman, Qatar and Saudi Arabia. The results showed that the level of satisfaction with satisfying basic needs of the study sample was high and close in the three countries, while the level of dissatisfaction was moderate with some disparity between them. There was a clear pattern of correlations between the level of satisfaction or dissatisfaction related to the extent to which basic needs are satisfied and both mental health and depressive symptoms. Multiple regression analysis showed that the level of mental health of university students in the three countries can be predicted from their degree of satisfaction with satisfying their basic psychological needs. The study concluds that satisfying the basic psychological needs of university students contributes to achieving mental health and that the lack of satiation is linked to the emergence of depressive symptoms.